Transition of plastic deformation mechanisms governed by spacing of nano-precipitates in a high entropy alloy. (August 2022) - Liu, Liyuan; Zhang, Yang; Ma, Jingming; Shang, Yongxuan; Han, Jihong; Li, Junpeng; Zhang, Zhongwu
Abstract: Optimization of the plastic deformation mechanism by reducing the stacking fault energy (SFE) of alloys through precipitation is a promising method to improve the strength–plasticity synergy of high-entropy alloys (HEAs). In this study, two HEAs with the same composition but different deformation mechanisms were developed by controlling precipitation. The dislocation plane slip and stacking fault (SF)-dominated deformation were tuned to be the main deformation mechanisms in the two HEAs. The transition of the deformation mechanism was induced by a change in the spacing ( λ ) of nano-precipitates. Only at sufficiently small λ (< 6 nm), the regions with reduced SFE around nano-precipitates connected and overlapped owing to the depletion of Ni and Nb, reducing the SFE of the whole matrix. This promoted the formation of SFs during deformation, thereby simultaneously improving strength and plasticity. Graphical abstract: Image, graphical abstract .